The Impact of Employee Job Satisfaction towards Employee Job Performance at PT.Y - Devilan Sutjitra (iBuss Management, 2015)
This research is done to analyze The Impact of Employee Job Satisfaction towards Employee Job Performance at PT.Y. The decreasing in employee job performance for the past 3 years has indicated the author to analyze the impact of employee job satisfaction towards job performance. The elements that used are 9 job satisfactions to measure the impact of satisfaction at PT.Y. The author got 100 respondents from PT.Y and use simple random sampling method.The analysis technique that used in this research is multiple linear regression analysis to describe the relationship between job satisfaction and job performance. The result of this research is show significant impact of employee job satisfaction towards employee job performance.  Keywords: Job satisfaction, Job performance, Employee, Spector’s Theory